2021
DOI: 10.1038/s41598-021-87998-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection of aptamers against triple negative breast cancer cells using high throughput sequencing

Abstract: Triple-negative breast cancer is the most aggressive subtype of invasive breast cancer with a poor prognosis and no approved targeted therapy. Hence, the identification of new and specific ligands is essential to develop novel targeted therapies. In this study, we aimed to identify new aptamers that bind to highly metastatic breast cancer MDA-MB-231 cells using the cell-SELEX technology aided by high throughput sequencing. After 8 cycles of selection, the aptamer pool was sequenced and the 25 most frequent seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The use of NGS for this purpose is highly advantageous over conventional Sanger DNA sequencing, since the number of possible reads can be increased from a few to millions. Using NGS, there is a much greater possibility of selecting highly specific aptamers from among those generated by cell-SELEX [ 39 , 45 ]. Further, when high throughput sequencing is combined with bioinformatics analysis, other information, besides a large pool of potential aptamer candidates, can be derived, such as the number of total reads, frequencies of every unique sequence and the rate of molecular enrichment [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of NGS for this purpose is highly advantageous over conventional Sanger DNA sequencing, since the number of possible reads can be increased from a few to millions. Using NGS, there is a much greater possibility of selecting highly specific aptamers from among those generated by cell-SELEX [ 39 , 45 ]. Further, when high throughput sequencing is combined with bioinformatics analysis, other information, besides a large pool of potential aptamer candidates, can be derived, such as the number of total reads, frequencies of every unique sequence and the rate of molecular enrichment [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mfold web server (version 3.0, accessed on 17 July 2022) was used to calculate the Gibbs free energy (∆G) and secondary structures of the sequences considering the primer and random regions, presenting an estimate of the optimal structure for each aptamer. The conditions used for the structure predictions were set according to the SB constitution (137 mM Na + and 1.4 mM Mg 2+ at pH 7.4) at 37 °C [ 39 ]. These sequences were aligned and the phylogenetic tree was constructed using the Tree Builder function in Geneious, that allowed the determination of the tree distances and sequence relatedness using a neighbor-joining model.…”
Section: Methodsmentioning
confidence: 99%
“…These predictions can provide not only information about the conformation of the secondary structure of aptamers but also information on Gibbs free energy to judge the stability of the structure formed by aptamers. Typically, more structurally stable aptamers are selected for aptamer truncation and further applications [ 58 ]. Several researches have shown that the loop regions of aptamers are useful in most aptamer-target interactions.…”
Section: Post-selex Optimization Of Aptamersmentioning
confidence: 99%
“…DNA aptamers are single-stranded DNA oligonucleotides that, through their unique three-dimensional (3D) structures, can be used for both selective binding to specific target molecules and can also elicit a functional effect upon binding and thus represent a promising molecular tool in this arena. Highly selective DNA aptamers are emerging as the most promising candidates for targeting the cell surface and intracellular target proteins. They have gained increasing attention for cancer diagnosis and treatment because of their low molecular weight, lack of or low immunogenicity, versatility in terms of manipulation for improved stability, and target efficacy . Aptamers are generally isolated by the SELEX (Systematic Evolution of Ligands by EXponential enrichment) process. , SELEX is typically carried out for a single target protein in solution and by repeated rounds of selection and enrichment using PCR amplification. One possible drawback of SELEX is inefficient enrichment of sequences, i.e., less-structured nonbinding sequences, that can be more easily amplified by PCR polymerases .…”
Section: Introductionmentioning
confidence: 99%